Tc-99m sestamibi gated SPECT in patients with left bundle branch block - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2001)
Purpose: The purpose of this study was to assess the diagnostic role of a Tc-99m sestamibi gated SPECT technique in patients with left bundle branch block (LBBB) without known coronary artery disease. Materials and Methods: Twenty consecutive patients with constant complete LBBB were included. A same-day rest-stress protocol was used, and dipyridamole stress (14 patients) or treadmill exercise (6 patients) was applied. Electrocardiograph (ECG)-gated SPECT images were acquired 15 minutes after the administration of 0.31 mCi/kg Tc-99m sestamibi at peak stress. Regional myocardial perfusion was analyzed in relation to the cardiac cycle. Results: Eleven of 14 patients who underwent a dipyridamole stress test had hypoactivity in the left anterior descending (LAD) artery territory in the ungated (summed) stress-rest images (abnormality ratio, 78%). On the ungated images, the abnormality was completely reversible in one patient (9%), partially reversible in five patients (46%), irreversible in two patients (18%), and reverse perfusion was identified in three patients (27%). Abnormality ratios of end-systolic and end-diastolic data were 93% and 29%, respectively. Conversely, the ungated rest-stress and end-systolic images of all the patients who performed treadmill exercise were abnormal despite the presence of normal or nearly normal end-diastolic myocardial perfusion. The angiographic findings correlated best with those of end-diastolic images. In 13 patients without coronary artery disease, normal or nearly normal regional perfusion was observed on end-diastole, but four patients with abnormal end-diastolic perfusion, which involved the LAD territory in all but one, had substantial coronary artery disease. The number of the involved segments was similar on the end-systolic and ungated data. Most of these artifactual defects were localized to the anteroseptal, septal, and inferoseptal segments. Conclusions: These preliminary data indicate that end-diastolic images can significantly reduce artifactual defects in patients with LBBB. The resolution of an LBBB pattern on end-diastolic data would significantly improve the diagnostic role of myocardial perfusion studies in these patients.
Keywords: artifacts; coronary artery disease; gated SPECT; left bundle branch block; Tc-99m sestamibi; EMISSION COMPUTED-TOMOGRAPHY; CORONARY-ARTERY DISEASE; MYOCARDIAL PERFUSION; TL-201 SCINTIGRAPHY; GLUCOSE-UTILIZATION; EXERCISE TL-201; PET; ABNORMALITIES; DIPYRIDAMOLE; METABOLISM